CORAK AJARAN TASAWUF DALAM PÊPALI KI AGÊNG SELO DITINJAU DARI PERSPEKTIF HERMENEUTIK FRIEDRICH DANIEL ERNST SCHLEIERMACHER - Ronika, Rima (UIN Sunan Kalijaga Yogyakarta, 2019)
Ki Ageng Selo was a Javanese philosopher who lived in the Demak Kingdom. At that time, the kingdom of Demak was ruled by Sultan Trenggono (1521-1545). Ki Agêng Selo’s Pêpali reflects the changing times of religion. Ki Agê̂ng Selo’s philosophy of life is influenced by his background in religion, philosophy and way of life expand his influence on the people, who are experiencing a turmoil in his life, as a result of the power struggle between the teachings of Hinduism and Islam. The philosophy of the life of Ki Agê̂ng Selo, as well as the philosophy of the Wali Sanga, is a synthesis of the religious elements brought by Islam and the elements of Hinduism. Just as the Walisanga did, by marrying between the teachings of Islam and the local culture (in this case Hindu culture), the teachings of Islam can be easily and strongly integrated.